"AFGHANISTAN IN THE GRIP OF THE TALIBAN”: THE STRUCTURE OF ARABIC NEWS HEADLINE - Yusuf, Kamal; Karimah, Siti Ismu Wahyul; Haikal Khan, Syifauddin; Falabiba, Wardah Fitrotul Maula (Arabi : Journal of Arabic Studies, 2022)
News from online media portals has advantages over traditional media in establishing credibility and influencing its readers. This study aims to investigate the structure of Arabic online media discourse in the header: Ø£ÙØºØ§Ù†Ø³ØªØ§Ù† ØªØØª ØÙƒÙ… Ø·Ø§Ù„Ø¨Ø§Ù†: Ø§Ù„Ø£Ù…Ù… Ø§Ù„Ù…ØªØØ¯Ø© ØªØ¬Ù…Ø¹ Ù…Ù„ÙŠØ§Ø± Ø¯ÙˆÙ„Ø§Ø± Ù„Ù„Ù…Ø³Ø§Ø¹Ø¯Ø§Øª Ø§Ù„Ø¥Ù†Ø³Ø§Ù†ÙŠØ© on the news portal www.bbc.arabic.com. This study employs a descriptive qualitative method in conjunction with Teun A. van Dijk's critical discourse analysis theory. The findings of this study indicate that the discourse structure of Arabic online media under the heading: Ø£ÙØºØ§Ù†Ø³ØªØ§Ù† ØªØØª ØÙƒÙ… Ø·Ø§Ù„Ø¨Ø§Ù†: Ø§Ù„Ø£Ù…Ù… Ø§Ù„Ù…ØªØØ¯Ø© ØªØ¬Ù…Ø¹ Ù…Ù„ÙŠØ§Ø± Ø¯ÙˆÙ„Ø§Ø± Ù„Ù„Ù…Ø³Ø§Ø¹Ø¯Ø§Øª Ø§Ù„Ø¥Ù†Ø³Ø§Ù†ÙŠØ© meets the criteria established by Teun A. van Dijk's model of discourse structure analysis, which includes macro structure (overall meaning of the text by fathoming the topic), superstructure (sees the text based on its plot), and microstructure (which examines the word choice, sentence structure, and writing style).